2013
DOI: 10.1007/s00436-013-3721-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the effect of diclazuril on second-generation merozoites of Eimeria tenella

Abstract: Diclazuril has long been used as an effective benzeneacetonitrile anticoccidial for the control of Eimeria tenella that causes coccidiosis. However, the molecular mechanism underlying the anticoccidial effects of diclazuril remains elusive. In this study, a proteomic analysis of the effect of diclazuril on second-generation merozoites of E. tenella was performed. Using two-dimensional gel electrophoresis and real-time quantitative polymerase chain reaction (RT-PCR), 13 target proteins were found to be signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…To date, no exhaustive proteomic analysis of the ROPK library has been published on the developmental stages analyzed in the present study to support our analysis. However, some proteomic data are available on sporozoites [ 15 , 34 , 35 , 36 , 37 ] and merozoites [ 36 , 38 , 39 ]. Previous publications demonstrated that the higher transcription of Etrop75 , Etrop5400 , Etrop5840 , Etrop5905 , Etrop26495 , Etrop27695 , and Etrop28765 observed in merozoites in the present study is confirmed at the protein level [ 36 , 38 ], and the higher transcription of Etrop27700 in sporozoites is consistent with proteomic data [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no exhaustive proteomic analysis of the ROPK library has been published on the developmental stages analyzed in the present study to support our analysis. However, some proteomic data are available on sporozoites [ 15 , 34 , 35 , 36 , 37 ] and merozoites [ 36 , 38 , 39 ]. Previous publications demonstrated that the higher transcription of Etrop75 , Etrop5400 , Etrop5840 , Etrop5905 , Etrop26495 , Etrop27695 , and Etrop28765 observed in merozoites in the present study is confirmed at the protein level [ 36 , 38 ], and the higher transcription of Etrop27700 in sporozoites is consistent with proteomic data [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…При этом он не вызывает угнетения естественного иммунитета, а механизм его действия до конца не изучен. Наиболее чувствительны к препарату неполовозрелые стадии эндогенного цикла развития кокцидий [12,13,14].…”
Section: The Influence Of Unicoccidum Application On the Quality Of Punclassified
“…using the transposome-based Nextera system) or the number of cells required for RNAseq (Gertz et al, 2012;Vollmers et al, 2015), as well as improved host genomic resources to screen out contaminating material, will offer further refinements. Improvements in proteomic technologies now allow validation of transcriptomic data and definition of post-transcriptional variation (Lal et al, 2009;Oakes et al, 2013;Shen et al, 2014b). …”
Section: Transcriptomic Analysesmentioning
confidence: 99%